Analisis Implementasi Kebijakan Dalam Pengelolaan Kawasan Perbatasan Negara di Provinsi Kepulauan Riau - Mirza Mirza; Siti Aisyah (Universitas Terbuka, 2020)
This research aimed to anlayze the implementation of border management policies in Riau Islands Province, which at the provincial level, state border management policies were coordinated through government bureaus and borders. Research problems included the coordination of the implementation of state border development programs that have not yet been integrated, the weakness of institutional institutions that oversaw national border policies and the needs for commitment by state administrators to be carried out in the form of programs/ activities in border areas. This study used a qualitative approach with descriptive methods. Data analysis was conducted based on George Edward III's Policy Implementation theory, covering aspects of communication, resources, disposition and bureaucratic structure. The conclusion of this study was that the implementation of sectoral coordination and ego was still a problem, including bureaucratic fragmentation with diffused subjects, making implementation of policies less directed and integrated. Strengthening the border issues became the development program in the Riau Islands Provincial Government to to improve the welfare of the people in the border areas. The program should be then included in the Regional Development Plan (RPJMD).